Management of Iatrogenic Urorectal Fistulae in Men with Pelvic Cancer - Martins, F (2017)
INTRODUCTION: Urorectal fistula (URF) is a devastating complication of pelvic cancer treatments and a surgical challenge for the reconstructive surgeon. We report a series of male patients with URF resulting from pelvic cancer treatments, specifically prostate (PCa), bladder (BCa), and rectal cancer (RCa), and explore the differences and impact on outcomes between purely surgical and non-surgical treatment modalities. METHODS: Between October 2008 and June 2015, 15 male patients, aged 59-78 years (mean 67), with URF induced by pelvic cancer treatments were identified in our institutions. Patients with a history of diverticulitis, inflammatory bowel disease, or other benign conditions were excluded. We reviewed the patients' medical records for symptoms, diagnostic tests performed, type and etiology of the fistula, type of surgical reconstruction, followup, and outcomes. RESULTS: Fourteen patients underwent surgical reconstruction. One patient developed metastatic disease before URF repair and, therefore, was excluded from this study. Mean followup (FU) was 32.7 months (14-79). All patients received diverting colostomy and temporary urinary diversion. An exclusively transperineal approach was used in nine (64.3%) patients and a combined abdominoperineal in five (35.7%). Overall successful URF closure was achieved in 12 (85.7%) patients, nine (64.3%) of whom at the first reconstructive attempt, two (14.3%) after two attempts (in our institution), and one (7.1%) after three attempts (two of which elsewhere). An interposition flap was used in seven (50%) patients. Surgical reconstruction failed ultimately in two (14.3%) patients who still have a colostomy and do not wish any further reconstruction. CONCLUSIONS: Our study has several limitations, including its retrospective nature and the heterogeneity of our small patient cohort. Nonetheless, although surgical reconstruction of URF may be extremely difficult and complex in the non-surgical/energy ablation patients, its successful reconstruction is possible in most through a transperineal, or a more aggressive abdominoperineal, approach with tissue interposition in selected patients.